Enhanced Pharmacokinetics of Factor VIIa as a Monomeric Fc Fusion. Issue 5 (May 2015) - Salas, Joe; Liu, Tongyao; Lu, Qi; Kulman, John D.; Ashworth, Tamera; Kistanova, Elena; Moore, Nancy; Pierce, Glenn F.; Jiang, Haiyan; Peters, Robert
Abstract Recombinant Factor VIIa (rFVIIa) is utilized for on-demand treatment of bleeding episodes in hemophilia patients with neutralizing antibodies (inhibitors) against Factor VIII or Factor IX, but a short half-life in the circulation ( 2.5 hrs) limits its use in a prophylactic setting. Recombinant FVIIa variants with improved pharmacokinetic properties may enable improved treatment and prevention of bleeding episodes in the inhibitor population. In this study we describe recombinant FVIIaFc (rFVIIaFc), a recombinant Fc-fusion protein generated to utilize the neonatal Fc receptor (FcRn)-mediated recycling pathway that protects immunoglobulin G from catabolism. On the basis of activity, rFVIIaFc exhibited a 5.5-fold extension in terminal half-life in hemophilia A mice compared to rFVIIa. The potency of rFVIIaFc was comparable to that of rFVIIa in thrombin generation assay and ROTEM. In agreement with these data, rFVIIaFc and rFVIIa showed similar acute efficacy at comparable molar doses in the tail clip bleeding model in hemophilia A mice. Taken together, these studies demonstrate enhanced pharmacokinetics and similar hemostatic properties for rFVIIaFc compared to rFVIIa.